Use by geterocycle derivate thioamides for selective extraction of palladium(II) from solutions HCl and HNO3 - E. V. Volchkova; T. M. Buslaeva; A. D. Shutalev; S. S. Guravleva (Тонкие химические технологии, 2006)
The extraction of Pd(II) from acid solution HCl by derivate tioamide has been studied. The possibility separate Pd(II) and Pt(IV); Pd(II) and Ag(I) has been demonstration. The coordination mexanusm extraction has been suggested